Modified screening and management strategies for chronic rhinosinusitis in hematologic patients receiving hematopoietic stem cell transplantation - Yen-Hui Lee; Chih-Feng Lin; Te-Huei Yeh; Huai-Hsuan Huang; Yi-Tsen Lin (Journal of the Formosan Medical Association)
Objectives: Given the lack of consensus on the screening and treatment for chronic rhinosinusitis (CRS) in the patients undergoing hematopoietic stem cell transplantation (HSCT), we reviewed the risk factors for CRS to improve the efficiency of sinonasal screening and analyzed the effect of treating CRS in search of guidance for modifying current management strategies for rhinosinusitis in HSCT patients. Methods: We conducted a nested case-control study in a retrospective cohort of hematologic patients receiving HSCT from April 2011 to April 2021 and collected data on demographics, smoking/atopic status, hematological diseases, and features of rhinosinusitis for analysis. The associated factors for control of rhinosinusitis and survival were analyzed. Results: Fifty-eight CRS patients were identified, and another 116 age- and sex-matched controls were selected from HSCT patients without CRS. Allergy and smoking were risk factors for CRS in HSCT patients. The multivariable logistic analysis indicated that endoscopic sinus surgery (ESS) was an independent factor for better control of CRS. However, survival was not associated with rhinosinusitis-related factors, but only with hematologic-related factors, including allogenic HSCT, reduced-intensity conditioning, and remission. Conclusion: Sinonasal evaluation should be targeted to the high-risk group. ESS is effective in managing CRS, while control of CRS is not determinant of overall survival in patients receiving HSCT.